Tag for UWB Chipless RFID: a single antenna approach - Hossain, A. K. M. Zakir; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (IEEE, 2015)
Even though the UWB passive RFID is getting so much attention for the researchers with the goal of replacing the conventional barcode system, the tag dimension still remains as a big issue which makes the tag price comparatively higher than the barcode. Many proposals have been made for last one decade to overcome this problem. In this paper an approach has been made to combine two different methods with the aim to reduce the tag dimensions. Both, the new tag and the existing tag are simulated in the CST MWS. It has been observed that with the new design, a reduction of 15.5% and 6% are found in terms of the width and length respectively and that leads to a reduction in occupied area around 20%.